A retroperitoneal supra-adrenal non-communicating gastric duplication cyst: a case report and comprehensive literature review - Mahmood Masud Al Awfi; Zainab Nasser Al Balushi; Suad Rashid Al Jahdhami; Mahmoud Hatem Sherif; Sareyah Al Sibai (SpringerOpen, 2021)
Abstract Background Gastric duplication cyst is a rare congenital anomaly. It is usually located in close proximity to the stomach. Nevertheless, there have been seldom reports in the literature that describe unusual locations. Retroperitoneal gastric duplications cysts are extremely rare and are usually confused with renal or adrenal cysts. Case presentation In this case report, we are presenting a 2-year-old girl with a complaint of bouts of abdominal pain, found to have a retroperitoneal supra-adrenal cyst on imaging. She underwent laparoscopic resection of the cyst with uneventful post-operative course. The histopathological diagnosis was surprisingly gastric duplication cyst. Conclusion In our review of the literature, the variability of this condition and its clinical manifestation are apparent. We also conclude that this diagnostic entity should be part of the differential diagnosis of intraperitoneal or retroperitoneal cysts and that laparoscopic resection of retroperitoneal cysts is the preferred approach.